IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE TO SUPPORT THE DEFENSE INDUSTRY: (STUDY AT PT. DOK AND KODJA BAHARI (PERSERO) JAKARTA) - Ahmad, Ahmad; Panji Suwarno; Djamarel Hermanto; Susilo Adi Purwantoro (International Journal of Social Science, 2023)
This research focuses on the implementation of Good Corporate Governance at PT Dok and Kodja Bahari (Persero) Jakarta to support the defense industry. This research is based on agency theory and the theory of Good Corporate Governance. The research method used in this study is a qualitative method with a descriptive approach. In this study, the research subject to be used was purposive sampling in determining the informants. The data analysis steps used in this study are the Analysis Interactive Model from Miles and Huberman, which divides the steps in data analysis activities into several parts: data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the study stated that the implementation of GCG at PT DKB was quite good even though some had not been implemented as example from SPI before GCG still making reports that were not by the evaluation of the Audit Committee or other divisions, in this case, such as lack of documentation or written reports, then after GCG implementation is an obligation that must be implemented. Likewise, if there are matters related to problems that must be coordinated with the audit committee or other divisions, SPI will make a request letter in terms of coordination related to these problems. While the implementation of GCG at PT DKB still requires improvement and follow-up as a result of the Assessment results report, this requires support from all stakeholders and aspects of the company's organization, but the company still wants to always work hard to make this happen.